1997
DOI: 10.1200/jco.1997.15.10.3230
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genomic damage in colorectal cancer by DNA fingerprinting: prognostic applications.

Abstract: The degree of genomic damage assessed by unbiased DNA fingerprinting correlates with genotypic, phenotypic, and clinical variables in colorectal carcinoma and may be useful in assessing prognosis in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
2
33
2
Order By: Relevance
“…Other groups have demonstrated that the degree of genomic damage assessed by arbitrarily primed PCR DNA fingerprinting correlates with genotypic, phenotypic and clinical variables in colorectal cancer and may be useful in assessing prognosis in that cancer type. 38 In contrast, use of traditional PCR amplification of multiple microsatellite markers to detect microsatellite instability is laborintensive and may be marker-dependent. Although microsatellite instability has been detected in small fractions in some cancer types, e.g., lung cancer 40,41 and several forms of leukemia, 42,43 reports of the microsatellite instability phenotype in breast cancer are inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…Other groups have demonstrated that the degree of genomic damage assessed by arbitrarily primed PCR DNA fingerprinting correlates with genotypic, phenotypic and clinical variables in colorectal cancer and may be useful in assessing prognosis in that cancer type. 38 In contrast, use of traditional PCR amplification of multiple microsatellite markers to detect microsatellite instability is laborintensive and may be marker-dependent. Although microsatellite instability has been detected in small fractions in some cancer types, e.g., lung cancer 40,41 and several forms of leukemia, 42,43 reports of the microsatellite instability phenotype in breast cancer are inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…This heterogeneity is probably responsible for the failure of otherwise effective therapeutic strategies (Heppner and Miller, 1998;Leith and Dexter, 1986;Vinyals et al, 1999). It is assumed that a correlation exists between increased genomic damage and malignant behavior (Arribas et al, 1997;Kern et al, 1989). Different molecular approaches have been used to quantify the extent of genomic disruption along the tumor and its association with identifiable clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Broad di erences are observed from sample to sample and also regarding the sign of the deregulation (up or down). The increased DDTF associated to advanced Dukes' stages and lymph node invasion appears as a predictable relationship due to the accumulated genomic damage that also accompanies these phenotypes (Arribas et al, 1997). Besides the correlation of a higher gene deregulation with more invasive stages, the index of di erential expression appeared to be an independent prognostic factor.…”
mentioning
confidence: 91%
“…Di erent studies have unveiled the extent of the genomic damage sustained by the tumor cell in human colorectal cancer (Kokal et al, 1986;Thein et al, 1987;Vogelstein et al, 1988;Delattre et al, 1989;Dutrillaux et al, 1995;Ried et al, 1996;Arribas et al, 1997). Genetic alterations accumulate during tumor progression and appear as a consequence of the instabilization of the genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation